EFEKTIVITAS TIGA BAHAN ORGANIK TERHADAP SERANGAN HAMA, PERTUMBUHAN DAN PRODUKSI SAWI (VIABEL: Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2024)
Pakcoy mustard greens are a type of rain-resistant vegetable. Pakcoy has green leaves with high nutritional content and economic value. One of the efforts that can be made to increase plant production is by providing fertilizer. Fertilization is carried out in order to meet the nutrient needs of plants, so that they can provide high yields, especially using organic fertilizer so that you can use waste as fertilizer. One type of recycled waste that can be used as organic fertilizer is egg shells, tea dregs and banana peels, each of which contains elements that are good for cultivation. Apart from that, pak choy mustard plants have the main problem that causes damage to pak choy, namely destructive pests that eat pak choy leaves such as plutella caterpillars, tritip caterpillars, armyworms, aphids (Aphids), cabbage spanner caterpillars. This research will be carried out from October to December 2023 at the UNISKA Integrated Field Laboratory. With a height of 67 meters above sea level, the temperature is 31.2◦C, humidity is 62.3% and soil pH is 6. Based on the research results, it shows that there is a very real influ.ence on the observed variables of plant height and number of leaves at the age of 14, 21 and 28 DAP, and it has an effect significant in root length at 28 days after planting. Fresh weight, dry weight, and armyworm pest attacks were lowest at P7.